Is there hope for Uncle Sam? : beyond the American bubble - Nederveen Pieterse, Jan (Zed Books, 2008)
For over a century now, America has dominated global politics and the global imagination. Yet as the dollar declines, inequality increases, rates of consumption are unprecedented and American unilateralism comes under fire, such hegemony is increasingly unsustainable. In this provocative new book, leading sociologist Jan Nederveen Pieterse asks whether it?s possible for America to chart a different course.